Minimum Design Loads and Associated Criteria for Buildings and Other Structures. - (ASCE), American Society of Civil Engineers (Standards Ser., 2021)
Standard ASCE/SEI 7-22 provides requirements for general structural design and includes means for determining various loads and their combinations, which are suitable for inclusion in building codes and other documents.